Effects of phospholipase D during cultured osteoblast mineralization and bone formation. Issue 4 (15th October 2018) - Abdallah, Dina; Skafi, Najwa; Hamade, Eva; Borel, Mathieu; Reibel, Sophie; Vitale, Nicolas; El Jamal, Alaeddine; Bougault, Carole; Laroche, Norbert; Vico, Laurence; Badran, Bassam; Hussein, Nader; et al.
Abstract: Mammalian phospholipase D (PLD) mostly hydrolyzes phosphatidylcholine producing phosphatidic acid. PLD activity was previously detected in different osteoblastic cell models, and was increased by several growth factors involved in bone homeostasis. To confirm possible actions of PLD isoforms during mineralization process, we analyzed their effects in osteoblastic cell models and during bone formation. PLD1 expression, along with PLD activity, increased during differentiation of primary osteoblasts and Saos‐2 cells, and peaked at the onset of mineralization. Subsequently, both PLD1 expression and PLD activity decreased, suggesting that PLD1 function is regulated during osteoblast maturation. In contrast, PLD2 expression was not significantly affected during differentiation of osteoblasts. Overexpression of PLD1 in Saos‐2 cells improved their mineralization potential. PLD inhibitor Halopemide or PLD1‐selective inhibitor, led to a decrease in mineralization in both cell types. On the contrary, the selective inhibitor of PLD2, did not affect the mineralization process. Moreover, primary osteoblasts isolated from PLD1 knockout (KO) mice were significantly less efficient in mineralization as compared with those isolated from wild type (WT) or PLD2 KO mice. In contrast, bone formation, as monitored by high‐resolution microcomputed tomography analysis, was not impaired in PLD1 KO nor in PLD2 KO mice, indicating that the lack of PLD1 or that of PLD2 did not affect the bone structure in adult mice. Taken together, our findings indicate that PLD activity, especially which of PLD1 isoform, may enhance the mineralization process in osteoblastic cells. Nonetheless, the lack of PLD1 or PLD2 do not seem to significantly affect bone formation in adult mice. Abstract : Phospholipase D (PLD) activity especially that of PLD1 isoform stimulated the mineralization process at the cellular level in our model osteoblastic cells. Nonetheless, the lack of PLD1 or PLD2 do not seem to significantly affect bone formation in adult mice.